2009
DOI: 10.4062/biomolther.2009.17.4.353
|View full text |Cite
|
Sign up to set email alerts
|

Simvastatin Induces Osteogenic Differentiation and Suppresses Adipogenic Differentiation in Primarily Cultured Human Adipose-Derived Stem Cells

Abstract: -Recent in vitro and in vivo animal studies have reported that statin, a cholesterol-lowering drug, stimulate osteogenic differentiation. In the present study, we investigated the effect of simvastatin on osteogenic and adipogenic differentiation in primarily cultured human adipose-derived stem cells (hADSCs). The simvastatin treatment significantly increased the positive cell numbers in alkaline phosphatase and von Kossa staining, and enhanced the expression levels of bone morphogenic protein (BMP)-2, core bi… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

0
3
0

Year Published

2021
2021
2023
2023

Publication Types

Select...
4

Relationship

0
4

Authors

Journals

citations
Cited by 4 publications
(3 citation statements)
references
References 31 publications
(26 reference statements)
0
3
0
Order By: Relevance
“…Various cell tests were performed in MSCs to evaluate the biological stability and function of the obtained products. According to the literature, Sim showed the best cell proliferation and bone differentiation ability at 1 μM [ 33 , 34 , 35 ]. Thus, in the current study, we developed GS complexes with the concentration of Sim at around 1 μM to evaluate the cellular responses.…”
Section: Resultsmentioning
confidence: 99%
“…Various cell tests were performed in MSCs to evaluate the biological stability and function of the obtained products. According to the literature, Sim showed the best cell proliferation and bone differentiation ability at 1 μM [ 33 , 34 , 35 ]. Thus, in the current study, we developed GS complexes with the concentration of Sim at around 1 μM to evaluate the cellular responses.…”
Section: Resultsmentioning
confidence: 99%
“…The research of Liu et al also has the same result, which shows that simvastatin of 0.01–1 μM can significantly promote the expression of osteogenic genes such as RUNX2 and OCN in hADSCs . Sun et al confirmed that 1 μM simvastatin could induce the expression of BMP-2, core binding factor alpha 1, and type I collagen of hADSCs and inhibit the adipogenic differentiation of hADSCs via down-regulating the expression of adipogenic genes such as PPARγ. Therefore, we conclude that 1 μM may be the optimal concentration for simvastatin to induce osteogenic differentiation of hADSCs.…”
Section: The Appropriate Simvastatin Concentration For Osteogenesismentioning
confidence: 74%
“…Statins promote osteoblasts to synthesize BMP2, a growth factor that causes osteoblasts to differentiate, proliferate, mature, and form new bone in vitro and in vivo , as well as inhibits adipocyte differentiation. [ 16 ]…”
Section: Discussionmentioning
confidence: 99%